Prediction of postoperative myocardial injury in patients undergoing laparoscopic pheochromocytoma/paraganglioma resection: protocol for an ambispective cohort study - Yuguang Huang; Yuelun Zhang; Ling Lan; Yi Zhang; Ye Ma; Le Shen; Yifei Zhao; Yaohan Li (BMJ Open)
Introduction Pheochromocytoma/paraganglioma (PPGL) resection remains a high-risk surgical procedure owing to severe haemodynamic instability, which can lead to myocardial injury after non-cardiac surgery (MINS). MINS is the most common and easily overlooked cardiovascular complication and results in increased postoperative mortality and prolonged inpatient hospitalisation. We aimed to develop and validate a predictive model for MINS in patients undergoing laparoscopic PPGL resection.Methods and analysis The PPGL-MINS study is a single-centre, observational, ambispective cohort study that includes patients undergoing elective laparoscopic PPGL resection under general anaesthesia at the Peking Union Medical College Hospital (PUMCH) between 1 January 2013 and 31 May 2025. We expect to enrol 700 patients, including at least 550 patients retrospectively and 150 patients prospectively. A prediction model will be developed for the retrospective cohort (training cohort) of patients from 1 January 2013 to 31 December 2022. Possible clinically relevant variables, particularly intraoperative blood pressure and heart rate, will be selected as candidate predictors. Stepwise and least absolute shrinkage and selection operator regression will be used for predictor selection. Multivariate logistic regression will be used to develop the prediction model, which will be presented as a nomogram. The developed model will be used to assess discrimination with the receiver operating characteristic curve and area under the curve value, calibration with the Hosmer-Lemeshow test and calibration curve, and clinical usefulness with decision curve analysis. Internal validation will be assessed with bootstrap. For external validation, we will use an independent prospective cohort (validation cohort) of patients from 1 March 2023 to 31 May 2025.Ethics and dissemination The study protocol has been approved by the Research Ethics Committee of PUMCH (IRB-K2893). Written informed consent will be obtained from all participants in the prospective cohort before enrolment in the study. We aim to publish and disseminate the findings in peer-reviewed journals and at scientific conferences.Trial registration number NCT05752773.